2017
DOI: 10.3390/brainsci7100125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prenatal and Subsequent Adult Alcohol Exposure on Pro-Inflammatory Cytokine Expression in Brain Regions Necessary for Simple Recognition Memory

Abstract: Microglia, the immune cells of the brain, are important and necessary for appropriate neural development; however, activation of microglia, concomitant with increased levels of secreted immune molecules during brain development, can leave the brain susceptible to certain long-term changes in immune function associated with neurological and developmental disorders. One mechanism by which microglia can be activated is via alcohol exposure. We sought to investigate if low levels of prenatal alcohol exposure can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 50 publications
3
21
1
Order By: Relevance
“…Taken together, our data are in line with previous reports demonstrating that chronic prenatal exposure to low-tomoderate doses of alcohol is sufficient to induce decreased behavioral reactivity in the open field (Kleiber et al, 2011) and declarative memory deficits in the novel object recognition test (Dandekar et al, 2019), together with a detrimental impact on the neuroimmune function of the perirhinal cortex (Terasaki and Schwarz, 2017). On the other hand, repeated low-dose prenatal alcohol exposure does not produce detrimental effects on pyramidal cells within the dorsal hippocampus or does not impair spatial learning and memory performance in the MWM (Cullen et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, our data are in line with previous reports demonstrating that chronic prenatal exposure to low-tomoderate doses of alcohol is sufficient to induce decreased behavioral reactivity in the open field (Kleiber et al, 2011) and declarative memory deficits in the novel object recognition test (Dandekar et al, 2019), together with a detrimental impact on the neuroimmune function of the perirhinal cortex (Terasaki and Schwarz, 2017). On the other hand, repeated low-dose prenatal alcohol exposure does not produce detrimental effects on pyramidal cells within the dorsal hippocampus or does not impair spatial learning and memory performance in the MWM (Cullen et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the PAE sex-specific differences in chemokines/cytokines, the same report demonstrated increased levels of CD11b and brain-derived neurotropic factor in adult brain examined on PND 90 ( 51 ). These data indicate that long-term immune activation in different brain regions does not require a parallel induction of cytokines.…”
Section: Animal Models Of Pae Reveal Basal Neuroimmune Changesmentioning
confidence: 76%
“…In a more recent study, PAE rats were further exposed to an acute binge-like dose of alcohol in adulthood ( 51 ). This study revealed that PAE exaggerated IL-6 production in the prefrontal cortex following alcohol exposure in adulthood, suggesting that adult alcohol exposure may act as a neuroinflammatory agent.…”
Section: Moderate Pae Shapes Neuroimmune Responses To Subsequent Inflmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility for this outcome is that the single acute ethanol challenge administered here was not optimal for revealing such prenatal-postnatal interactions based on the dose utilized (i.e., we may be observing a ceiling effect after a 4 g/kg administration) or time point examined (i.e., PAE may alter the kinetics of the immune response to acute challenge and we did not select an optimal time to capture PAE vs. FCL effects in response to the challenge). To fully reveal lingering PAE effects, repeated exposures to ethanol might be required to observe more significant consequences of PAE (e.g., similar to the two consecutive ethanol binges in Terasaki and Schwarz, 2017), or there may be other time points (e.g., withdrawal; Topper et al, 2015) at which PAE effects would be more evident. Furthermore, it is possible that other brain regions, such as the prefrontal cortex (Terasaki and Schwarz, 2017), might be more sensitive to lasting effects of PAE on cytokines and chemokines, and their responsiveness to acute ethanol.…”
Section: Discussionmentioning
confidence: 99%